2012
DOI: 10.1111/j.1601-183x.2012.00774.x
|View full text |Cite
|
Sign up to set email alerts
|

Somatic markers mediate the effect of serotonin transporter gene polymorphisms on Iowa Gambling Task

Abstract: This study investigated whether somatic markers mediate the effect of serotonin transporter genotype on Iowa Gambling Task (IGT) performance. Participants (N = 135) were genotyped for the insertion/deletion and singlenucleotide (rs25531) polymorphisms in the promoter region of the serotonin transporter gene (5-HTTLPR). The results of mediation analyses indicated that skin conductance responses that anticipated IGT card selections partially (i.e. 42% of the total effect) mediated the effect of genotype on IGT p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 42 publications
3
25
0
Order By: Relevance
“…For example, in Caucasians, previous biallelic studies indicated the s/s genotype was highly associated with post-traumatic stress disorder (PTSD) (Kilpatrick et al 2007;Lee et al 2005), but with the consideration of rs25531, the L L genotype became the risk genotype for developing this disorder (Grabe et al 2009). Consistently, our study in Han Chinese population also considered rs25531, and indicated the L L genotype showed poorer IGT performance, which is in line with Miu et al (2012) studies in Caucasians.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…For example, in Caucasians, previous biallelic studies indicated the s/s genotype was highly associated with post-traumatic stress disorder (PTSD) (Kilpatrick et al 2007;Lee et al 2005), but with the consideration of rs25531, the L L genotype became the risk genotype for developing this disorder (Grabe et al 2009). Consistently, our study in Han Chinese population also considered rs25531, and indicated the L L genotype showed poorer IGT performance, which is in line with Miu et al (2012) studies in Caucasians.…”
Section: Discussionsupporting
confidence: 90%
“…Consistently, our study in Han Chinese population also considered rs25531, and indicated the L′L′ genotype showed poorer IGT performance, which is in line with Miu et al . () studies in Caucasians.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…These researchers provided support for a mediational model in which 5-HTTLPR contributed to social anxiety symptoms via decreased reappraisal. Another study indicated that negative self-reflection provokes stronger personal distress in SS than in LL individuals [ 14 ]. Compared to the LL individuals, SS individuals report higher levels of emotional reactivity (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis [31], which included ten genetic association studies, supported an attentional bias to threat with medium effect size in S'S' genotypes, but not in S'L' or L'L' genotypes. Not surprisingly, this meta-analysis [31] genotyping were performed using published protocols [32,33] …”
mentioning
confidence: 99%